Prevalence of Anti-Thyroid Peroxidase Antibody in Hypothyroid Patients Visiting Western Regional Hospital: A Cross-Sectional Study - Bastola, Basanta Kumar; Regmi, Kiran; Poudel, Rajendra; Thapa, Suresh; Thakuri, Surya Bahadur Hamal; Sharma, Soniya (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: Hypothyroidism is a common endocrine disorder with autoimmune thyroiditis increasing as a major cause, especially in iodine-sufficient areas. Anti-thyroid peroxidase antibody is hallmark of autoimmune thyroid disease. This study aims to determine the prevalence of anti- TPO antibodies in hypothyroid patients and their correlation with the type of hypothyroidism, age, gender, and clinical presentation.Methods: This is an analytical cross-sectional study conducted among 73 hypothyroid patients presenting to OPD and medical ward of Western Regional Hospital, a tertiary care centre in Gandaki Province. Demographic and clinical data were collected. Laboratory assessments included thyroid function tests and anti-TPO levels using chemiluminescence immunoassay. Descriptive and inferential statistics were applied using Statistical Package for the Social Sciences version 27.Results: Among 73 participants, 28(38%) were positive for anti-TPO antibody. The mean age was 42.1 ± 12.07 years, and 81% patients were female. Among patients with overt hypothyroidism, 41% were anti-TPO positive, while 36% of subclinical hypothyroid patients had anti-TPO positivity. There were no statistically significant associations between anti-TPO status and gender (p=0.821), type of hypothyroidism (p=0.666), or age group (p=0.24). Likewise, the common presenting signs and symptoms did not have statistically significant association with the TPO positivity status.Conclusions: Over one-third of hypothyroid patients had anti-TPO antibody positivity, with a slightly higher prevalence in overt hypothyroidism. However, demographic and clinical variables did not significantly correlate with antibody status.